Inserting Teaching Local Culture as Character Building in Teaching English Speaking - Pipit Muliyah (Journal of Applied Linguistics (ALTICS), 2021)
This study is aimed at having critical analysis in teaching English as a foreign language which generally does not give much attention in teaching local culture especially intercultural communication. Promoting the character building as character education in the teaching learning process (TLP) is one of the instructional objectives. Commonly, the current belief in English TLP is only inserting foreign cultural values which do not always match with our own culture. Moreover, the exits activity and material do not represent character education. Here, for instance, there is an absence of explicit statements about character aspects that are needed to be included in students' activities. Dealing with the main learning objective (LO) of our national education, the current belief should be changed by integrating our local culture (Indonesian) in English TLP to achieve national education goals in promoting character building. It is mainly purposed to maintain, encourage and build spirit of nationalism individually or nationally. Keywords: character building, local culture, teaching English